Pengujian Kadar Antosianin Bunga Pagoda (Clerodendrum paniculatum L.) Berdasarkan Variasi Penambahan Asam - Meytha Putri Dewanty; Livia Syafnir; Vinda Maharani Patricia (UNISBA Press, 2024)
Abstract. Anthocyanin is a natural coloring that belongs to the flavonoid group. Pagoda flowers have anthocyanins which can be separated by choosing an extraction method to find out the right extraction to induce the highest levels of anthocyanins in pagoda flowers because anthocyanins are unstable compounds. This research aims to determine the level of pagoda flowers. Anthocyanin levels were determined using a differential pH strategy with Uv-Vis spectrophotometry. The results of determining the concentration of anthocyanin levels in pagoda flowers in 1% HCl were 8,75 mg/100 g and in potassium acetate they were 1,20 mg/100g. Abstrak. Antosianin merupakan warna alami yang termasuk dalam golongan flavonoid. Bunga pagoda mempunyai antosianin yang dapat dipisahkan dengan memilih metode ekstraksi untuk mengetahui ekstraksi yang tepat untuk menginduksi kadar antosianin tertinggi pada bunga pagoda karena antosianin merupakan senyawa tidak stabil. Penelitian ini bertujuan untuk menentukan kadar pada bunga pagoda . Kadar antosianin ditentukan menggunakan strategi pH diferensial dengan spektrofotometri Uv-Vis. Hasil penetapan konsenterasi kadar antosianin bunga pagoda pada HCl 1% adalah sebesar 8,75 mg/100 g dan pada kalium asetat adalah sebesar 1,20 mg/ 100g.